2018
DOI: 10.3892/mmr.2018.8529
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from guava fruit protect renal tubular endothelial cells against acetaminophen‑induced cytotoxicity

Abstract: Acetaminophen (APAP) is an analgesic and antipyretic agent primarily used in the clinical setting. However, high doses of APAP can cause oxidative stress. Guavas have been reported to provide anti‑inflammatory, anti‑microbial, anti‑oxidative and anti‑diarrheal functions. In addition, guavas have been reported to prevent renal damage due to progression of diabetes mellitus. Therefore, the aim of the present study was to investigate whether guavas can reduce APAP‑induced renal cell damage. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Guava extracts were prepared as described [1]. Briefly, extracts from the mature stage of the red guava fruit were used in this study.…”
Section: Guava Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Guava extracts were prepared as described [1]. Briefly, extracts from the mature stage of the red guava fruit were used in this study.…”
Section: Guava Extract Preparationmentioning
confidence: 99%
“…Many studies have demonstrated that guava extracts have anti-inflammatory, anti-microbial, anti-oxidative and anti-cancer activities [1][2][3]. These functions of guava extracts are related to numerous bio-active molecules such as beta-caryophyllene oxide, vitamins, tannins, phenolic compounds, flavonoids and triterpenoid acids [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%